TAREKAT TIJANIYAH DI KALIMANTAN SELATAN - Syafruddin . (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2011)
Tijaniyah tarekat including one fast-growing tarekat in South Kalimantan. At first the congregation is growing in South Kalimantan in 1995, brought by KH Ahmad Ansari is based in the city of Banjarmasin, then spread to various areas in South Kalimantan, Central Kalimantan and even into the Bangkas island. In South Kalimantan there are 21 tarekat and majelis taklim 4 shrines, with the number of followers of about 15,000 people. Tijaniyah congregation has its own characteristics when compared with other tarekat, namely: a) it takes a new format of tarekat, because Ahmad at-Tijani did not require his followers showed the attitude of excessive piety, and he emphasizes the presence of an interpreter intercessor between man and God. It was Ahmad at-Tijani itself. b) It has simple and clear wirid; c) Ahmad at-Tijani recognition reaches two positions, namely as a guardian Qutbb al-Aqthab and khatm al-Waliyah; d) prohibits its followers to follow as membership other institutes; e) it has no pedigree. Even if there are genealogy is shorter than the other tarekat, and f) this tarekat prohibits its followers to smoke because it is considered as najis.